Efficiency of the coastal filter: Nitrogen and phosphorus removal in the Baltic Sea. (13th September 2017) - Asmala, Eero; Carstensen, Jacob; Conley, Daniel J.; Slomp, Caroline P.; Stadmark, Johanna; Voss, Maren
Abstract: An important function of coastal ecosystems is the reduction of the nutrient flux from land to the open sea, the coastal filter. In this study, we focused on the two most important coastal biogeochemical processes that remove nitrogen and phosphorus permanently: denitrification and phosphorus burial. We compiled removal rates from coastal systems around the Baltic Sea and analyzed their spatial variation and regulating environmental factors. These analyses were used to scale up denitrification and phosphorus burial rates for the entire Baltic Sea coastal zone. Denitrification rates ranged from non‐detectable to 12 mmol N m −2 d −1, and correlated positively with both bottom water nitrate concentration and sediment organic carbon content. The rates exhibited a strong decreasing gradient from land to the open coast, which was likely driven by the availability of nitrate and labile organic carbon, but a high proportion of non‐cohesive sediments in the coastal zone decreased the denitrification efficiency relative to the open sea. Phosphorus burial rates varied from 0.21 g P m −2 yr −1 in open coastal systems to 2.28 g P m −2 yr −1 in estuaries. Our analysis suggests that archipelagos are important phosphorus traps and account for 45% of the coastal P removal, while covering only 17% of the coastal areas. High burial rates could partly be sustained by phosphorus import from the open Baltic Sea. We estimate that the coastal filter in the Baltic Sea removes 16% of nitrogen and 53% of phosphorus inputs from land.